Affordable Excellence : The Singapore Healthcare Story - Haseltine, William A. (Book collections on Project MUSE., 2013)
This is the story of the Singapore healthcare system: how it works, how it is financed, its history, where it is going, and what lessons it may hold for national health systems around the world. Singapore ranks sixth in the world in healthcare outcomes, yet spends proportionally less on healthcare than any other high-income country. This is the first book to set out a comprehensive system-level description of healthcare in Singapore, with a view to understanding what can be learned from its unique system design and development path. The lessons from Singapore will be of interest to those currently planning the future of healthcare in emerging economies, as well as those engaged in the urgent debates on healthcare in the wealthier countries faced with serious long-term challenges in healthcare financing. Policymakers, legislators, public health officials responsible for healthcare systems planning, finance and operations, as well as those working on healthcare issues in universities and think tanks should understand how the Singapore system works to achieve affordable excellence.